IMPLEMENTASI TQM DALAM MENINGKATKAN MUTU PENDIDIKAN DI MTs. ISTIQOMAH TALAMAU KABUPATEN PASAMAN BARAT - Alwizra Alwizra (IAIN Batusangkar, 2020)
This research discussed abaut the Implementation of TQM at MTs. Istiqomah Talamau in improving the quality of education. This research has purposes: to know the process of TQM implemantation in improving the quality of education, to know the characteristic of TQM that has been implemented, to know changes that was occured in the quality of a education after the implementation of TQM, and to know trouble that was occured in implementation of TQM to improve the quality of education at MTs Istiqomah Talamau. This research used qualitatif research approach, and the type of research that was used was etnography. This research has been done at MTs Istoqomah Talamau Kabupaten Pasaman Barat. The sources of data in this research was: the source of data directly from MTs Istiqomah Talamau, the source of data was not direct that was the data which was transferred the data to data collector. Data collection technique used observation, interview, and document collection. Data analisis technique used Miles and Huberman data model. The result of this resech found out: the Implementation of TQM used four steps, these are: Quality planning management, Program implementation management, Management control, Activity evaluation management. Then, the Implementation of of TQM’s characteristic that was applied at MTs. Istiqomah Talamau was: Costomer satisfication, Improving product quality, Respecting to every people, Building a team work, and implementating the improvements countinously.